Evaluation of Reporting Methods for Assessment and Surgical Planning of Perianal Fistulas - Sarra Kharbech (22501886) (2025)
Perianal fistula is a complex condition where surgeons conduct surgeries based on the mentally mapped images they created from the information found in the radiology report. If not properly treated, a fistula could reoccur. To reduce the chances of reoccurrence, a patient-specific, visual, and accurate depiction of the internal tracts in relation to the pelvic floor is required. A three-dimensional (3D) parametric model generation software was previously developed and evaluated successfully with radiologists. In this paper, the software output is evaluated with two colorectal surgeons for 10 fistula cases. The paper compares three reporting different modes: (1) 3D models only, (2) conventional radiology report and picture archiving and communication system (PACS) magnetic resonance (MR) images, and (3) 3D models + standardized radiology report. The percentage of agreement between surgeons across cases and cognitive load are the primary metrics used for evaluation. Mode 3 superseded both modes 1 and 2, meaning that surgeons prefer to see a 3D model along with a standardized report to plan a case’s surgical intervention. Mode 1 superseded mode 2, which also shows surgeons preference to inspect a 3D model rather than inspecting cases the conventional way. Surgeons’ agreement in opinions across cases in mode 3 was 85%, whereas it was 18% and 5% in mode 1 and mode 2, respectively. This shows that information was conveyed more consistently across surgeons in mode 3. NASA TLX tests show that surgeons had the least cognitive load while working with mode 3, followed by mode 1 and then mode 2. Overall, the findings indicate that 3D models, even without radiologists’ written input, outperform the current standard practice of delivering unstructured radiology reports alongside raw PACS images. Other Information Published in: Journal of Imaging Informatics in Medicine License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10278-025-01524-4